Prevalence of Xerostomia in Population-based Samples: A Systematic Review - M.F. Orellana, DDS, PhD; M.O. Lagravere, DDS, MSc; D.GJ. Boychuk, DDS; (Blackwell Synergy, 2006)
The consequences of xerostomia on oral health have been studied for decades; however, the actual prevalence of this disorder on the general population remains controversial.